Lithium ion battery positive electrode active material and preparation method thereof
By providing a specific positive electrode active material for composite oxide lithium-ion batteries, the chemical displacement and integral area ratio of characteristic peaks of magic angle rotating solid nuclear magnetic resonance (MAS ssNMR) is optimized to optimize the local environment of lithium ions, and the layered oxide is solved by solving the problem of layered oxides using magic angle rotation solid nuclear magnetic resonance (MAS ssNMR) The problem of insufficient circulation stability of the positive electrode active material while increasing its capacity has achieved higher discharge capacity and cycle stability.
Patent Information
- Application Number
- CN202310955166.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-01
- Publication Date
- 2025-02-14
AI Technical Summary
While the existing layered oxide positive electrode active materials have insufficient cyclic stability and safety performance, especially at high voltages, the cyclic stability of the material is not satisfactory.
Provide a positive electrode active material of composite oxide lithium ion battery, whose general formula is LiaNibMncMdNeOf, and shows no less than two characteristic peaks through magic angle rotation solid nuclear magnetic resonance (MAS ssNMR). The chemical shift of characteristic peak 1 is located at 600~800ppm. The chemical shift of characteristic peak 2 is located at -50~50 ppm, the integral area of peak 1 is S1, the integral area of peak 2 is S2, and S1/S2>1000. The material optimizes the local environment of lithium ions through specific composition and doping treatments and reduces the deintercalation barrier.
This material significantly improves the discharge capacity and cycle stability of lithium-ion batteries, can maintain better performance at high voltages, and solves the problem of insufficient cycle stability of existing materials.
Smart Images

Figure BDA0004369644440000071 
Figure BDA0004369644440000072
Abstract
Description
Technical Field
[0001] The invention belongs to the field of manufacturing positive electrode materials for lithium ion batteries, and in particular relates to a positive electrode active material, a preparation method thereof and a lithium ion battery comprising the same. Background Art
[0002] Lithium-ion batteries have become an indispensable part of human society in the fields of digital, energy storage, electric vehicles, etc. due to their high energy density and flexible applicability. After years of development, the positive active materials that make up lithium-ion batteries have gradually evolved from the initial lithium cobalt oxide to three major types of materials: olivine structure materials such as lithium iron phosphate, layered oxide materials such as lithium nickel cobalt manganese oxide, and spinel structure materials such as lithium nickel manganese oxide. Among them, whether in power lithium-ion batteries or non-power lithium-ion batteries, layered oxide positive active materials occupy an important position in the positive active material market due to their good cycle performance, high capacity and voltage.
[0003] Due to the continuous market demand for higher energy density lithium-ion batteries, how to improve the capacity of layered oxide positive electrode active materials is becoming a key issue to be solved. It is generally believed that, as described in ACS Energy Lett., 2017, 2, 196-223, the role of nickel is to improve the capacity of the material; the role of cobalt is to stabilize the layered structure of the material, reduce lithium-nickel mixing, and improve the stability of the material during long cycles; the role of manganese is to reduce material costs, improve material safety and structural stability. In ternary layered oxide positive electrode active materials, there are two main ways to achieve high capacity: one is to increase the nickel content, but with the increase in nickel content, the cycle stability and safety performance of the material have become new challenges; the other is to increase the working voltage of the material. For example, the working voltage of lithium-rich layered positive electrode active materials can be increased to as high as 4.8V, and the capacity can reach more than 260mAh / g, but at high voltage, the cycle stability of the material is not satisfactory enough.
[0004] The capacity of the positive electrode active material is achieved by the migration of lithium ions between the positive electrode and the negative electrode. In theory, the lithium ions that constitute the positive electrode active material should all be able to be removed. However, due to the influence of the local environment of lithium ions in the positive electrode active material and the high chemical bond energy between lithium ions and adjacent atoms or ions, a higher voltage is often required to drive more lithium ions out, into the electrolyte, and then transferred to the negative electrode. Nuclear magnetic resonance (NMR) is an effective test method for systematically characterizing the bonding between atoms and adjacent atoms. NMR is a phenomenon in which the spin nucleus with a fixed magnetic moment absorbs electromagnetic waves of a specific frequency under the action of a constant magnetic field and an alternating magnetic field, transitions from a lower energy level to a higher energy level, and exchanges energy with the alternating magnetic field. In a material or a molecule, the same atomic nucleus has different resonant frequencies due to the different chemical environments it is in, and exhibits different chemical shifts. The main reason for this phenomenon is the presence of an electron cloud around the nucleus. In different chemical environments, the density of the electron cloud around the nucleus is different. For positive electrode active materials, if the local chemical environment of lithium ions is different, the effective capacity they can exert will also be different.
[0005] Therefore, a considerable number of effectively transferable lithium ions are obtained, which is more conducive to the positive electrode active material to exert high capacity and maintain better cycle performance. Summary of the invention
[0006] In view of the shortcomings of the prior art, the object of the present invention is to provide a lithium ion battery positive electrode active material, a preparation method thereof, and a lithium ion battery comprising the same. The lithium ion battery according to the present invention has high capacity and excellent cycle performance.
[0007] According to a first aspect of the present invention, there is provided a positive electrode active material for a lithium ion battery, wherein:
[0008] The lithium ion battery positive electrode active material is composed of the general formula Li a Ni b Mn c M d N e O f A composite oxide represented by, wherein 0.9≤a≤1.5, 0<b≤1, 0≤c≤1, 0≤d≤1, 0≤e≤1, 1.8≤f≤2.2, b+c+d+e=1, and the values of a, b, c, d, e and f satisfy the requirement that the composite oxide is electrically neutral, and M is at least one selected from Co, Fe, Cu, Mo, W, Zn, Cr, Al and Ti;
[0009] N is at least one selected from S, Na, Ca, Mg, Mo, Nb, Zr, V, Sc, P, Sr, Ba, Cl, F, Si, Ge, B, C and K;
[0010] in,
[0011] The composite oxide shows no less than two characteristic peaks under magic angle spinning solid nuclear magnetic resonance (MAS ssNMR), wherein the chemical shift of characteristic peak 1 is located at 600-800 ppm, and the chemical shift of characteristic peak 2 is located at -50-50 ppm, wherein the integral area of peak 1 is S1, the integral area of peak 2 is S2, and S1 / S2>1000.
[0012] Preferably, the chemical shifts of the characteristic peaks of the composite oxide are preferably 650 to 750 ppm for peak 1 and -10 to 10 ppm for peak 2.
[0013] Preferably, the composite oxide is LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.90 Co 0.05 Mn 0.05 O2 or LiNi 0.9 Al 0.1 O2.
[0014] Preferably, the composite oxide is in a granular form, and the median particle size, ie, D50, is 3 to 18 μm, preferably 5 to 15 μm.
[0015] Preferably, the BET specific surface area of the composite oxide is 0.1 to 2 m 2 / g.
[0016] Preferably, the composite oxide is further doped with a compound containing one or more elements selected from Ca, Mg, Zr, Sr, Na, Si, Al, La, W, B, Fe, Cu, K, Ge, Nd, Nb, Mo, Y or Ce, and is particularly preferably doped with oxides of the above elements.
[0017] Preferably, the molar ratio of the Li element to the doping element in the doped composite oxide is 1:0.0001-0.01, more preferably 1:0.0005-0.005.
[0018] Preferably, the composite oxide is further coated with a compound comprising one or more elements selected from Ca, Mg, Zr, Sr, Na, Si, Al, La, W, B, Fe, Cu, K, Ge, Nd, Nb, Mo, Y and Ce, and more preferably coated with an oxide thereof.
[0019] Preferably, the weight of the compound of the element used for coating is 100 to 5000 ppm, more preferably 500 to 3000 ppm, relative to the total weight of the composite oxide before coating.
[0020] Preferably, the residual lithium hydroxide of the composite oxide is less than 4000 ppm, and the residual lithium carbonate is less than 4000 ppm.
[0021] According to a second aspect of the present invention, there is provided a method for preparing the positive electrode active material of a lithium ion battery according to the present invention, the method comprising the following steps:
[0022] Step 1: Ni b Mn c M d N e (OH) f Mix well with LiOH·H2O or lithium carbonate;
[0023] Step 2: The mixture obtained in step 1 is sintered in an oxygen-containing atmosphere.
[0024] The method for preparing the positive electrode active material of the present invention, wherein in step 1, Ni b Mn c M d N e (OH) f The molar ratio of the lithium ion battery to the LiOH·H2O or the Li element in lithium carbonate is 1:1.01 to 1:1.10, preferably 1:1.02 to 1:1.05.
[0025] In the method for preparing the positive electrode active material of the present invention, the sintering temperature in step 2 is 700° C. to 1000° C.; and the sintering time is 8 hours to 14 hours.
[0026] Preferably, in the method for preparing the positive electrode active material of the present invention, the mixture obtained in step 1 can be further doped: in step 1, a compound containing one or more elements selected from Ca, Mg, Zr, Sr, Na, Si, Al, La, W, B, Fe, Cu, K, Ge, Nd, Nb, Mo, Y or Ce is added and mixed evenly, preferably an oxide containing one or more elements selected from Ca, Mg, Zr, Sr, Na, Si, Al, La, W, B, Fe, Cu, K, Ge, Nd, Nb, Mo, Y or Ce is added.
[0027] Preferably, the molar ratio of the Li element to the doping element in the doped mixture is 1:0.0001-0.01, more preferably 1:0.0005-0.005.
[0028] Preferably, the method for preparing the positive electrode active material of the present invention further comprises step 3 after step 2:
[0029] Step 3: Coating treatment, adding a compound containing one or more selected from the elements Ca, Mg, Zr, Sr, Na, Si, Al, La, W, B, Fe, Cu, K, Ge, Nd, Nb, Mo, Y and Ce to the product obtained in step 2, and mixing them evenly, and then sintering the obtained mixture again.
[0030] Preferably, the compound added in the coating treatment is an oxide.
[0031] Preferably, the weight of the compound of the element used for coating is 100 to 5000 ppm, more preferably 500 to 3000 ppm, relative to the total weight of the positive electrode active material of the lithium ion battery.
[0032] Preferably, in step 3), the sintering conditions are: sintering temperature is 300° C. to 500° C.; and sintering time is 4 hours to 12 hours.
[0033] According to a third aspect of the present invention, there is provided a lithium ion battery positive electrode, which comprises the lithium ion battery positive electrode active material according to the present invention.
[0034] According to a fourth aspect of the present invention, a lithium ion battery is provided, comprising the lithium ion battery positive electrode according to the present invention.
[0035] According to a fifth aspect of the present invention, there is provided use of the lithium ion battery positive electrode active material of the present invention in preparing a lithium ion battery positive electrode.
[0036] The positive effects of the present invention are:
[0037] The invention provides a positive electrode active material for a lithium ion battery. When the positive electrode active material shows no less than two characteristic peaks under magic angle spinning solid nuclear magnetic resonance (MASssNMR), the chemical shifts of the characteristic peaks are respectively located at 500-800 ppm (peak 1) and -50-50 ppm (peak 2), wherein the integral area of peak 1 is S1, the integral area of peak 2 is S2, and when S1 / S2>1000, the material has an excellent layered structure, a local environment where more lithium ions are located is conducive to lithium ion deintercalation, and has a lower deintercalation barrier. Compared with the prior art, the material shows higher discharge capacity and cycle stability. DETAILED DESCRIPTION
[0038] The present invention will be further described below by way of examples, but the present invention is not limited to the examples.
[0039] The main raw material information is as follows:
[0040] Nickel-cobalt-manganese hydroxide precursor, Zhongwei New Materials Co., Ltd.;
[0041] Lithium hydroxide monohydrate LiOH·H2O, 41.96 g / mol, Shandong Ruifu Lithium Industry Co., Ltd.,
[0042] Lithium carbonate Li2CO3, 73.89 g / mol, Shandong Ruifu Lithium Industry Co., Ltd.,
[0043] Polyvinylidene fluoride (PVDF), analytical grade, Aladdin,
[0044] Nitromethylpyrrolidone (NMP), analytical grade, Aladdin.
[0045] The main experimental and testing equipment information is as follows:
[0046] Laser particle size analyzer: Malvern Mastersizer 3000;
[0047] Surface area analyzer: Bestec 3H-2000A;
[0048] NMR: Bruker Avance 200MHz;
[0049] Electrochemical testing equipment: Shenzhen Xinwei button cell testing system;
[0050] Roasting equipment: Hefei Kejing tube furnace, model OTF-1500X.
[0051] The particle size D50 test method is as follows:
[0052] The material powder was taken and tested using a Malvern Mastersizer 3000 laser particle size analyzer with a wet sampler to obtain particle size distribution data.
[0053] 7 Li MAS SS-NMR test method is as follows:
[0054] The composite oxide powder was placed into a 1.3 mm MAS probe and tested at a rotation frequency of 60 kHz. 7 LiMAS SS-NMR. After subtracting the background from the characteristic peaks of the obtained spectrum, calculate the integrated area.
[0055] The electrochemical performance test method is as follows:
[0056] The composite oxide and lithium sheet obtained in the embodiment are respectively used as positive and negative active materials to assemble button cells; the positive electrode slurry in the positive electrode sheet is composed of positive electrode active material, acetylene black (conductive agent) and PVDF (binder), and the mass ratio of the three is 80:12:8; the button battery testing system of Shenzhen Xinwei is used for testing, and the charging and discharging voltage is a set voltage range, such as 3.0-4.5V. The button battery assembled with the positive electrode active material is subjected to electrochemical performance testing at room temperature, and the mass specific capacity of the positive electrode active material is tested at a current density of 0.02A / g (0.1C), and then its 100-cycle cycle performance is tested at a current density of 0.2A / g (1C), and its cycle retention rate is calculated.
[0057] Example 1
[0058] Make Ni 0.5 Co 0.2 Mn 0.3 (OH)2 and lithium carbonate were mixed evenly in a high-speed mixer at a molar ratio of 1:0.515, and the mixture was put into a sagger, placed in a tube furnace, and sintered at 920°C for 12 hours in an oxygen-containing atmosphere to obtain 102 g of composite oxide LiNi 0.5 Co 0.2 Mn 0.3 O2. The solid nuclear magnetic resonance peak position and peak area of the composite oxide were then calculated, and the electrochemical specific capacity and cycle performance of the lithium ion battery prepared using the composite oxide as the positive electrode active material were tested. The data are shown in Tables 1 and 2.
[0059] Example 2
[0060] Ni 0.90 Co 0.05 Mn 0.05 (OH)2 and LiOH·H2O were mixed evenly in a high-speed mixer at a molar ratio of 1:1.03, and the mixture was put into a sagger, placed in a tube furnace, and sintered at 720°C for 12 hours in an oxygen-containing atmosphere to obtain 101 g of composite oxide LiNi 0.90 Co 0.05 Mn 0.05 O2. The solid nuclear magnetic resonance peak position and peak area of the composite oxide were then calculated, and the electrochemical specific capacity and cycle performance of the lithium ion battery prepared using the composite oxide as the positive electrode active material were tested. The data are shown in Tables 1 and 2.
[0061] Example 3
[0062] Ni 0.9 Al 0.1(OH)2 and LiOH·H2O were mixed evenly in a high-speed mixer at a molar ratio of 1:1.03, and the mixture was put into a sagger, placed in a tube furnace, and sintered at 730°C for 12 hours in an oxygen-containing atmosphere to obtain 100 g of composite oxide LiNi 0.9 Al 0.1 O2. The solid nuclear magnetic resonance peak position and peak area of the composite oxide were then calculated, and the electrochemical specific capacity and cycle performance of the lithium ion battery prepared using the composite oxide as the positive electrode active material were tested. The data are shown in Tables 1 and 2.
[0063] Example 4
[0064] Make Ni 0.5 Co 0.2 Mn 0.3 (OH)2, lithium carbonate and Al2O3 were added to a high mixer in a molar ratio of 1:0.515:0.001, and mixed evenly using a high-speed mixer. The mixture was put into a sagger, placed in a tube furnace, and sintered at 920°C for 12 hours in an oxygen-containing atmosphere to obtain 102 g of Al-doped composite oxide LiNi 0.5 Co 0.2 Mn 0.3 O2. The above-doped LiNi 0.5 Co 0.2 Mn 0.3 O2 and 1000ppm equivalent of Y2O3 were mixed evenly using a high-speed mixer and sintered at 450°C for 8 hours in an oxygen-containing atmosphere to obtain a Y-coated Al-doped composite oxide LiNi 0.5 Co 0.2 Mn 0.3 O2. The solid nuclear magnetic resonance peak position and peak area of the Y-coated Al-doped composite oxide were then calculated, and the electrochemical specific capacity and cycle performance of the lithium-ion battery prepared using the composite oxide as the positive electrode active material were tested. The data are shown in Tables 1 and 2.
[0065] Comparative Example 1
[0066] Ni 0.5 Co 0.2 Mn 0.3 (OH)2 and lithium carbonate were mixed evenly in a high-speed mixer at a molar ratio of 1:0.515, and the mixture was put into a sagger, placed in a tube furnace, and sintered at 620°C for 12 hours in an oxygen-containing atmosphere to obtain 107 g of composite oxide LiNi 0.5 Co 0.2 Mn 0.3O2. The solid nuclear magnetic resonance peak position and peak area of the composite oxide were then calculated, and the electrochemical specific capacity and cycle performance of the lithium ion battery prepared using the composite oxide as the positive electrode active material were tested. The data are shown in Tables 1 and 2.
[0067] Comparative Example 2
[0068] Ni 0.90 Co 0.05 Mn 0.05 (OH)2 and LiOH·H2O were mixed evenly in a high-speed mixer at a molar ratio of 1:1.03, and the mixture was put into a sagger, placed in a tube furnace, and sintered at 520°C for 12 hours in an oxygen-containing atmosphere to obtain 114 g of composite oxide LiNi 0.90 Co 0.05 Mn 0.05 O2. The solid nuclear magnetic resonance peak position and peak area of the composite oxide were then calculated, and the electrochemical specific capacity and cycle performance of the lithium ion battery prepared using the composite oxide as the positive electrode active material were tested. The data are shown in Tables 1 and 2.
[0069] Comparative Example 3
[0070] Ni 0.9 Al 0.1 (OH)2 and LiOH·H2O were mixed evenly in a high-speed mixer at a molar ratio of 1:1.03, and the mixture was put into a sagger, placed in a tube furnace, and sintered at 1100°C for 12 hours in an oxygen-containing atmosphere to obtain 96 g of composite oxide LiNi 0.9 Al 0.1 O2. The solid nuclear magnetic resonance peak position and peak area of the composite oxide were then calculated, and the electrochemical specific capacity and cycle performance of the lithium ion battery prepared using the composite oxide as the positive electrode active material were tested. The data are shown in Tables 1 and 2.
[0071] Table 1
[0072]
[0073] Table 2
[0074]
[0075] It can be seen from Table 2 that:
[0076] By comparing Example 1 and Comparative Example 1, it can be found that the position of Peak 1 of the composite oxide in Comparative Example 1 is not in the range of 600-800 ppm, and S1 / S2 is less than 1000. At this time, the capacity of the lithium-ion battery prepared using the composite oxide of Example 1 as the positive electrode active material is much higher than that of Comparative Example 1, and the cycle retention rate is maintained at a high level.
[0077] By comparing Example 2 and Comparative Example 2, it can be found that the S1 / S2 of the composite oxide obtained in Comparative Example 2 is less than 1000. At this time, the capacity of the lithium-ion battery prepared using the composite oxide of Example 2 as the positive electrode active material is much higher than that of Comparative Example 2, and the cycle retention rate is maintained at a high level.
[0078] By comparing Example 3 and Comparative Example 3, it can be found that the S1 / S2 of the composite oxide obtained in Comparative Example 3 is less than 1000. At this time, the capacity of the lithium-ion battery prepared using the composite oxide of Example 3 as the positive electrode active material is much higher than that of Comparative Example 3, and the cycle retention rate is maintained at a high level.
[0079] This shows that, when the composite oxide provided by the present invention is used as a positive electrode active material for a lithium ion battery, when the composite oxide shows at least two characteristic peaks under solid nuclear magnetic resonance (MAS ssNMR), the chemical shifts of the characteristic peaks are respectively located at 600 to 800 ppm (peak 1) and -50 to 50 ppm (peak 2), and when S1 / S2>1000, the electrochemical performance of the lithium ion battery obtained by using the composite oxide as the positive electrode active material is significantly improved, the capacity is increased, and the cycle stability is enhanced.
[0080] It should be noted that the Ni content has an effect on the capacity of the lithium-ion battery. It is generally believed that the higher the Ni content, the higher the capacity of the lithium-ion battery. The capacity of the lithium-ion battery obtained by using the composite oxides of Comparative Examples 2 and 3 as the positive electrode active material is higher than that of Example 1, because the Ni content of the composite oxides of Comparative Examples 2 and 3 is higher than that of Example 1.
[0081] By comparing Example 1 and Comparative Example 1, Example 2 and Comparative Example 2, and Example 3 and Comparative Example 3 with the same composition, the capacity of the lithium ion battery prepared by using the positive electrode active material according to the present invention is significantly improved.
[0082] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention. Those skilled in the art will appreciate that, under the guidance of this specification, some modifications or adjustments may be made to the present invention. These modifications or adjustments should also be within the scope defined by the claims of the present invention.
Claims
1. A positive electrode active material for a lithium ion battery, wherein the positive electrode active material for a lithium ion battery is a material having a general formula Li a Ni b Mn c M d N e O f A composite oxide represented by 0.9≤a≤1.5, 0<b≤1, 0≤c≤1, 0≤d≤1, 0≤e≤1, 1.8≤f≤2.2, b+c+d+e=1, and the values of a, b, c, d, e and f meet the requirement that the composite oxide is electrically neutral, M is at least one selected from Co, Fe, Cu, Mo, W, Zn, Cr, Al and Ti; N is at least one selected from S, Na, Ca, Mg, Mo, Nb, Zr, V, Sc, P, Sr, Ba, Cl, F, Si, Ge, B, C and K; The composite oxide shows no less than two characteristic peaks under magic angle spinning solid nuclear magnetic resonance (MAS ssNMR), the chemical shift of characteristic peak 1 is located at 600-800 ppm, and the chemical shift of characteristic peak 2 is located at -50-50 ppm, wherein the integrated area of peak 1 is S1, the integrated area of peak 2 is S2, and S1 / S2>1000.
2. The positive electrode active material for lithium ion batteries according to claim 1, wherein: The chemical shift of the characteristic peak 1 of the composite oxide is located at 650 to 750 ppm, and the chemical shift of the characteristic peak 2 is located at -10 to 10 ppm.
3. The positive electrode active material for lithium ion batteries according to claim 1 or 2, wherein: The composite oxide is LiNi 0.5 Co 0.2 Mn 0.3 O2、LiNi 0.90 Co 0.05 Mn 0.05 O2 or LiNi 0.9 Al 0.1 O2.
4. The positive electrode active material for a lithium ion battery according to any one of claims 1 to 3, wherein The composite oxide is in granular form, and the median particle size, i.e., D50, is 3 to 18 μm, preferably 5 to 15 μm; Preferably, the BET specific surface area of the composite oxide is 0.1 to 2 m 2 / g; Preferably, the residual lithium hydroxide of the composite oxide is less than 4000 ppm or the residual lithium carbonate is less than 4000 ppm.
5. The positive electrode active material for a lithium ion battery according to any one of claims 1 to 4, wherein The composite oxide is further doped with a compound comprising one or more selected from the group consisting of Ca, Mg, Zr, Sr, Na, Si, Al, La, W, B, Fe, Cu, K, Ge, Nd, Nb, Mo, Y or Ce, preferably doped with an oxide comprising one or more selected from the group consisting of Ca, Mg, Zr, Sr, Na, Si, Al, La, W, B, Fe, Cu, K, Ge, Nd, Nb, Mo, Y or Ce; Preferably, the molar ratio of the Li element to the doping element in the doped composite oxide is 1:0.0001-0.01, more preferably 1:0.0005-0.
005.
6. The lithium ion battery positive electrode active material according to any one of claims 1 to 5, wherein The composite oxide is coated with a compound comprising one or more elements selected from the group consisting of Ca, Mg, Zr, Sr, Na, Si, Al, La, W, B, Fe, Cu, K, Ge, Nd, Nb, Mo, Y and Ce, preferably coated with an oxide comprising one or more elements selected from the group consisting of Ca, Mg, Zr, Sr, Na, Si, Al, La, W, B, Fe, Cu, K, Ge, Nd, Nb, Mo, Y and Ce; Preferably, the weight of the compound of the element used for coating is 100 to 5000 ppm, more preferably 500 to 3000 ppm, relative to the total weight of the composite oxide before coating.
7. A method for preparing a positive electrode active material for a lithium ion battery according to any one of claims 1 to 6, comprising the following steps: Step 1: Ni b Mn c M d N e (OH) f Mix well with LiOH·H2O or lithium carbonate; Step 2: sintering the mixture obtained in step 1 in an oxygen-containing atmosphere; Wherein, the sintering temperature in step 2 is 700° C. to 1000° C.; and the sintering time is 8 hours to 14 hours.
8. The method for preparing a positive electrode active material for a lithium ion battery according to claim 7, wherein: Step 1 Ni b Mn c M d N e (OH) f The molar ratio of the lithium ion battery to the LiOH·H2O or the Li element in lithium carbonate is 1:1.01 to 1:1.10, preferably 1:1.02 to 1:1.
05.
9. The method for preparing a positive electrode active material for a lithium ion battery according to claim 7 or 8, wherein: The mixture obtained in step 1 is further doped by adding a compound containing one or more elements selected from Ca, Mg, Zr, Sr, Na, Si, Al, La, W, B, Fe, Cu, K, Ge, Nd, Nb, Mo, Y or Ce in step 1 and mixing them uniformly; It is preferred to add an oxide containing one or more elements selected from Ca, Mg, Zr, Sr, Na, Si, Al, La, W, B, Fe, Cu, K, Ge, Nd, Nb, Mo, Y or Ce; Preferably, the molar ratio of the Li element to the doping element in the doped mixture is 1:0.0001-0.01, more preferably 1:0.0005-0.
005.
10. The method for preparing a positive electrode active material for a lithium ion battery according to any one of claims 7 to 9, wherein: The method for preparing a positive electrode active material for a lithium ion battery comprises step 3 after step 2, Step 3: coating treatment, adding a compound containing one or more elements selected from the group consisting of Ca, Mg, Zr, Sr, Na, Si, Al, La, W, B, Fe, Cu, K, Ge, Nd, Nb, Mo, Y and Ce to the product obtained in step 2, mixing them evenly, and then sintering the obtained mixture again; Preferably, the compound added in the coating treatment is an oxide; Preferably, the weight of the compound used for coating is 100 to 5000 ppm, more preferably 500 to 3000 ppm, relative to the total weight of the product obtained in step 2; Preferably, the sintering conditions in step 3 are: sintering temperature is 300° C. to 500° C.; and sintering time is 4 hours to 12 hours. 11 . A lithium ion battery comprising a positive electrode comprising the lithium ion battery positive electrode active material according to claim 1 .